HUMAN RESOURCE TALENT MANAGEMENT IN THE PUBLIC SECTOR - Qathrunnada Atikah Hamka; Haliah (CV. Radja Publika, 2025)
This study discusses the application of talent management in the context of public sector organizations using the theoretical framework of the Social Exchange System (SET). Through a literature review and a qualitative approach, the study highlights the importance of effective talent management strategies, including the fulfillment of psychological contracts and a supportive organizational culture, to improve the performance and retention of qualified employees. The results show that the success of talent management depends on the strategic mindset of talent managers who prioritize the process of recruiting, identifying, developing, and maintaining positive relationships with the talented workforce. Research recommendations include the development of an integrative model that combines these factors and the need for further studies in other sectors such as SOEs and companies listed on the IDX. These findings confirm that a comprehensive talent management approach can address public sector challenges such as workforce shortages and early retirement, thereby improving organizational performance and service quality.